Presurgical orthodontic treatment of patients with complete bilateral cleft lip and palate - Radojičić Julija (Vojnosanitetski Pregled, 2014)
Introduction. Cleft lips and palates are the most common congenital orofacial anomaly. This type of clefts is the most severe from the orthodontic-surgical therapy aspect. Case report. A female newborn with a complete cleft of the primary and the secondary palate was admitted to the clinic, where a multiple-role orthodontic device was specially designed and applied to primarily manage the closure of the existing cleft and help to improve the suckling ability of the baby. Besides the fact that it allows breastfeeding, it has a significant orthodontic effect, too. Conclusion. Specificity of this device is the lack of extraoral fixation. What can easily be observed is a progressive reduction of the cleft between the separated segments and the premaxilla retrusion. It, thus, allows the creation of much better conditions for further surgical management of the said defect.